2019
DOI: 10.46622/jogea.v2i1.2485
|View full text |Cite
|
Sign up to set email alerts
|

The Viability of a Bimodal Application of an Interactive-GIS-Tutor within Low-Resourced South African Schools

Abstract: Adhering to the United Nations’ call to implement Geographical Information Systems (GIS) education, GIS was phased into the South African Further Education and Training (FET) Geography curriculum over the period 2006-2008. Yet, following the global trend, the slow adoption rate of GIS education points to the presence of GIS implementation barriers, due to a lack of educational GIS research. This implies that GIS curriculum development has outpaced GIS educational research. To support Geography teachers, an Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The excerpts above show that sufficient time is key to implementing PBGIS in rural learning ecologies. This finding resonates with Fleischmann and Westhuizen (2015), who point out that time is significant for many reasons in GIS, such as the time required for teachers to attend professional development (PD) workshops to learn the necessary GIS software; the time required to develop or modify instructional materials supported by GIS; as well as the time required in the curriculum of geography subject to effectively teach learners about the technology. Tarisayi (2018) explains that time constraints in teaching of GIS in South Africa stem from the CAPS allocation of only four hours per week to teaching geography.…”
Section: Lack Of Teaching Timesupporting
confidence: 65%
See 1 more Smart Citation
“…The excerpts above show that sufficient time is key to implementing PBGIS in rural learning ecologies. This finding resonates with Fleischmann and Westhuizen (2015), who point out that time is significant for many reasons in GIS, such as the time required for teachers to attend professional development (PD) workshops to learn the necessary GIS software; the time required to develop or modify instructional materials supported by GIS; as well as the time required in the curriculum of geography subject to effectively teach learners about the technology. Tarisayi (2018) explains that time constraints in teaching of GIS in South Africa stem from the CAPS allocation of only four hours per week to teaching geography.…”
Section: Lack Of Teaching Timesupporting
confidence: 65%
“…This made teachers happy because their schools would not be left behind. A PBGIS initiative, managed by ESRI South Africa (Pty) Ltd., envisages the introduction of GIS to resource-poor (without electricity and/or computers) schools in South Africa (Breetzke et al, 2011;Kerski et al, 2013;Fleischmann & Westhuizen, 2015;Fleischmann & van der Westhuizen, 2020).…”
Section: Pbgis Implementation In Schoolsmentioning
confidence: 99%
“…They argue that there is no GIS education in secondary school curricula, shortage of experienced teachers, lack of knowledge and technical expertise, unwillingness of teachers to change their teaching mode, a shortage of funds, and inadequate resources. Fleischmann and van der Westhuizen (2019) concluded that there should be an infusion of interest and collaboration across borders to exchange knowledge and support.…”
Section: Introductionmentioning
confidence: 99%